1999
DOI: 10.2337/diacare.22.8.1245
|View full text |Cite
|
Sign up to set email alerts
|

High-dose vitamin E supplementation normalizes retinal blood flow and creatinine clearance in patients with type 1 diabetes.

Abstract: Oral vitamin E treatment appears to be effective in normalizing retinal hemodynamic abnormalities and improving renal function in type 1 diabetic patients of short disease duration without inducing a significant change in glycemic control. This suggests that vitamin E supplementation may provide an additional benefit in reducing the risks for developing diabetic retinopathy or nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
187
1
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 292 publications
(197 citation statements)
references
References 0 publications
6
187
1
3
Order By: Relevance
“…While our group and others have reported that there is a decrease in RBF in diabetic animal models and in patients with Type 1 diabetes [8,9,10,11], other groups have reported that diabetes increases RBF [44,45,46]. The different results from these groups could be related to the methodologies used (video fluorescein angiography and laser Doppler velocimetry), the duration of diabetes, whether or not clinically observable diabetic retinopathy was present, the blood glucose levels at the time of the measurement, and the level of glycaemic control or haemoglobin A 1c in the studied patients [20,47].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…While our group and others have reported that there is a decrease in RBF in diabetic animal models and in patients with Type 1 diabetes [8,9,10,11], other groups have reported that diabetes increases RBF [44,45,46]. The different results from these groups could be related to the methodologies used (video fluorescein angiography and laser Doppler velocimetry), the duration of diabetes, whether or not clinically observable diabetic retinopathy was present, the blood glucose levels at the time of the measurement, and the level of glycaemic control or haemoglobin A 1c in the studied patients [20,47].…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies have shown that treatment of DM rats with an endothelin type A receptor antagonist (BQ123), a PKCβ inhibitor (LY333531), or vitamin E could also ameliorate RBF abnormalities [10,27,30,31]. In addition, intravitreal injections of endothelin-1 or phorbol dibutyrate (an activator of PKC) rapidly induced retinal arteriole constriction and prolonged MCT, which mimicked diabetes [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This concept is supported by data showing that antioxidants such as vitamin E prevent some of the vascular dysfunction associated with diabetes in animal models (Kunisaki et al, 1995). In one study of diabetic patients, treatment with high-dose vitamin E for four months reversed diabetesinduced alterations in retinal blood flow (Bursell et al, 1999). However, studies on the effect of antioxidant supplementation in diabetic patients have largely been limited to examination of blood levels of biochemical markers of oxidative stress and other risk factors for retinopathy (Jain, 2006).…”
Section: 74mentioning
confidence: 88%
“…85,86 A recent clinical study demonstrated that short-term, high-dose oral vitamin E therapy normalized retinal and renal haemodynamics in diabetic patients with disease of less than 10 years duration despite no change in glycaemic control. 87 Whether these changes will eventually result in suppression of DR awaits a prospective, randomized clinical trial. Since overdosage with vitamin E can potentially result in toxicity, high doses of vitamin E should not be advocated until results of appropriate clinical trials are known.…”
Section: Antioxidantsmentioning
confidence: 99%